Tourism - an academic discipline (discursive article) - Butowski, Leszek (Turyzm/Tourism, 2012)
The article discusses the main methodological dilemmas connected with tourism as a field of academic research. The first part presents tourism as an area of interest in various academic disciplines. The second is a critical discussion on multidisciplinary and interdisciplinary approaches to the study of tourism. The third features an analysis of the methodological standpoints concerning possibilities for the autonomy of tourism as an academic discipline. The summary proposes a model of development for tourism studies aimed at the autonomy of academic tourism.